2015
DOI: 10.1007/s00262-015-1678-4
|View full text |Cite
|
Sign up to set email alerts
|

FoxP3+ and IL-17+ cells are correlated with improved prognosis in cervical adenocarcinoma

Abstract: Cervical adenocarcinoma comprises approximately 15 % of cervical cancer cases. This histological subtype has different characteristics than cervical squamous cell carcinoma, which may influence disease progression. To study whether the infiltration of T cell subpopulations was correlated with cervical adenocarcinoma patient survival, similar to squamous cell carcinoma, the tumor-infiltrating T cells, Tregs, Th17 cells and IL-17+ cell frequencies were analyzed in a cohort of cervical adenocarcinoma patients (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 46 publications
(48 reference statements)
4
53
0
Order By: Relevance
“…In contrast, we found EGFR upregulation exclusively in SCC [68]. Currently, we are focusing on understanding the immunological differences between SCC and AC, and we are investigating the presence of different immune cell subsets which may give us more information on the different role of HLA expression in these histological subtypes [3236]. In addition, there was more complete HLA-A loss in SCC metastasis, while there was more complete loss of HLA-B/C in AC metastasis, again emphasizing the need for better immune-characterization of the two major cervical cancer histological subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, we found EGFR upregulation exclusively in SCC [68]. Currently, we are focusing on understanding the immunological differences between SCC and AC, and we are investigating the presence of different immune cell subsets which may give us more information on the different role of HLA expression in these histological subtypes [3236]. In addition, there was more complete HLA-A loss in SCC metastasis, while there was more complete loss of HLA-B/C in AC metastasis, again emphasizing the need for better immune-characterization of the two major cervical cancer histological subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…For the detection and the characterisation of tumour-infiltrating T cells, we used a triple immunofluorescent staining, as previously described [15]. After antigen retrieval using Tris–EDTA buffer pH 9.0, whole sections were incubated overnight at 4 °C with the combination of primary antibodies, as detailed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…A recent phenotypic analysis of T H 17 cells revealed that they resembled terminally differentiated memory T-cells, and strongly promoted long-term anti-tumor immunity [29]. Increased T H 17 population was associated with a better prognosis in patients with cervical adenocarcinoma [30]. A cytokine macrophage inhibitory factor (MIF) that strongly promoted the generation of T H 17 was significantly associated with a better survival in patients with nasopharyngeal carcinomas [31].…”
Section: Does the Number Of T-cells In The Tumor Microenvironment Matmentioning
confidence: 99%